Analysis Of Leading Sectors In Central Java Province And Boyolali Regency Using Location Quotient, Shift Share, And Scalogram Methods - Ayuddyah, Ayuddyah Eko Syafitri Maharani; Anandhita Siregar,; Amalia Sulistiningsih,; Amanda Shinta Dyah Sulistyowati, (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
The purpose of this study is to determine the leading sector of the economy and classify the growth of the economic sector and the performance of the economic sector in Boyolali Regency. This study uses secondary data in the form of a time series of the Gross Regional Domestic Product (GRDP) of Boyolali Regency in 2012-2022. The analytical tools used in this study are: 1). Location Quotient (LQ) analysis is used to determine the base and non-base sectors in the Boyolali Regency economy. 2). Shift Share analysis is used to determine changes and shifts in the economic structure of Boyolali Regency. 3). Klassen Typology Analysis is used to get an overview of the pattern and structure of economic growth in Boyolali Regency. 4). Scalogram analysis is used to identify service centers based on the facilities owned by the Boyolali District. The results of the analysis of Location Quotient, Shift Share, Klassen Typology, and Scalogram show that the leading sector of Boyolali Regency in 2012-2022 is the one competitive leading sector, namely agriculture, forestry and fisheries. Then Boyolali Regency also has four competitive mainstay sectors, four competitive prospective sectors, and eight competitive backward sectors.